2009
DOI: 10.2500/ajra.2009.23.3266
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Novel Chitosan Gel on Hemostasis after Endoscopic Sinus Surgery in a Sheep Model of Chronic Rhinosinusitis

Abstract: In the sheep model of ESS, CD gel significantly improved hemostasis compared with the control at 2, 4, and 6 minutes after mucosal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
(54 reference statements)
0
28
0
2
Order By: Relevance
“…The development of a CD based hydrogel has led to a product suitable for surgical applications. This gel may be tailored to suit different areas of application and has shown to be effective in both haemostasis and adhesion reduction when used in the nasal cavity [9,10]. In this preliminary study, we demonstrate that a CD gel is well tolerated as an intra-abdominal agent with a highly statistically significant reduction in adhesion formation and with no increased risk of enterotomy dehiscence when compared to control groups.…”
Section: Discussionmentioning
confidence: 80%
“…The development of a CD based hydrogel has led to a product suitable for surgical applications. This gel may be tailored to suit different areas of application and has shown to be effective in both haemostasis and adhesion reduction when used in the nasal cavity [9,10]. In this preliminary study, we demonstrate that a CD gel is well tolerated as an intra-abdominal agent with a highly statistically significant reduction in adhesion formation and with no increased risk of enterotomy dehiscence when compared to control groups.…”
Section: Discussionmentioning
confidence: 80%
“…The hemostatic effectiveness of this biomaterial has led to the delivery of a 'HemCon' patch to all US soldiers on active duty in Iraq and Afghanistan. Recently, Valentine et al [45] and Athanasiadis et al…”
Section: Recent Advances In Biomaterialsmentioning
confidence: 98%
“…Chitosan dextran significantly improved wound healing and reduced adhesion formation compared to other topical agents . Chitosan dextran also significantly reduced intraoperative bleeding compared to no treatment control . Following this work in the sheep model, human study showed that intraoperative hemostasis was significantly less than untreated control side.…”
Section: Discussionmentioning
confidence: 79%
“…30 Chitosan dextran also significantly reduced intraoperative bleeding compared to no treatment control. 31 Following this work in the sheep model, human study showed that intraoperative hemostasis was significantly less than untreated control side. Postoperatively, the CD side showed significantly less adhesions than the control, with all other parameters (crusting, mucosal edema, infection, and granulation tissue) showing no difference between sides.…”
Section: Discussionmentioning
confidence: 95%